The Effect of Buffalo Milk Whey on Salmonella Populations in Chickens Infected with Salmonella sp. - M.K.Arjuna; N.Ginting; S.Pakpahan (Talenta Publisher, 2023)
Bacterial is one cause of health decreased on poultry especially chicken. This study aims to determine the effect of giving buffalo milk whey on the number of salmonella populations found in chickens infected with Salmonella sp. The study was conducted at the Animal Production laboratory, Faculty of Agriculture, and the Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Sumatera Utara. The design used was a non-factorial completely randomized design (CRD) with 4 treatments with 5 replications. Treatment consisted of P0 (control without whey administration), P1 (25% whey + 75% distilled water), P2 (50% whey + 50% distilled water), and P3 (antibiotic Colimas). Observation parameters were pH, antimicrobial bacterial test and number of Salmonella sp bacterial colonies. The results showed that the treatment had a real effect on pH, antimicrobial bacterial tests and the number of Salmonella sp bacterial colonies. In conclusion that giving buffalo milk whey to native chickens infected with Salmonella sp. with treatment of 50% buffalo whey + 50% distilled water can increase the pH and reduce the population of Salmonella sp. on chicken digestion so that it can replace the use of commercial antibiotics.